An introduction to British economic policy - Hare, Paul G.; Kirby, Maurice W. (Brighton, Sussex ; Wheatsheaf Books : Distributed by Harvester Press, 1984)
In this volume, the writer choses to be selective, concentrating on the particular aspects of economic policy of central concern to the British economy in the early 1980s. A novel feature of the book is the inclusion of contributions from a number of different academic departments.
Includes bibliographical references and index.
hza 27/06/2018
Loans
Keywords: Econmic policy; Great Britain